2012
DOI: 10.3389/fncom.2012.00050
|View full text |Cite
|
Sign up to set email alerts
|

Building Blocks of Self-Sustained Activity in a Simple Deterministic Model of Excitable Neural Networks

Abstract: Understanding the interplay of topology and dynamics of excitable neural networks is one of the major challenges in computational neuroscience. Here we employ a simple deterministic excitable model to explore how network-wide activation patterns are shaped by network architecture. Our observables are co-activation patterns, together with the average activity of the network and the periodicities in the excitation density. Our main results are: (1) the dependence of the correlation between the adjacency matrix a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
79
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(85 citation statements)
references
References 69 publications
(106 reference statements)
2
79
1
Order By: Relevance
“…Similarly to the study at hand, in our earlier work we have found that the amount of network bursts increases with the locality of the network (where also CC is correlated with the locality) [57] in a network of spontaneously active neurons. Our results are backed by [67], where the number of 3-node triangles (comparable to motif 13, see Fig. 1) in the graphs were positively correlated with the mean level of activity in a discrete-state model of neuronal networks.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Similarly to the study at hand, in our earlier work we have found that the amount of network bursts increases with the locality of the network (where also CC is correlated with the locality) [57] in a network of spontaneously active neurons. Our results are backed by [67], where the number of 3-node triangles (comparable to motif 13, see Fig. 1) in the graphs were positively correlated with the mean level of activity in a discrete-state model of neuronal networks.…”
Section: Discussionsupporting
confidence: 70%
“…In such networks, not only the local connectivity but also the connectivity pattern between the clusters would greatly affect the collective dynamics. This aspect is highly relevant when unraveling the function of a vertebrate brain, and ground-laying studies have already been carried out in the context of, e.g., emergence of sustained activity [67], [70]. Promising attempts were also done in [68], where a biologically inspired modular network model of the mammalian pre-Bötzinger complex was studied by computational means.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of work on collective activity patterns in neuronal systems [30][31][32][33][34][35]. This activity relates to proactive functions of the brain, e.g., attention and memory [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…A relative-threshold variant 148 (requiring a certain percentage of a node's neighbors to be active, in order to activate the node) was explored 149 in [46] and [47]. The deterministic limit of the model (p → 1, f → 0) has been analyzed in [48] and in much 150 detail in [6]. 151 In the biological implementation, the topological reinforcement rule was reformulated by using functional 152 connectivity as a surrogate of TO.…”
mentioning
confidence: 99%